CD47‐Mediated Hedgehog/SMO/GLI1 Signaling Promotes Mesenchymal Stem Cell Immunomodulation in Mouse Liver Inflammation. Issue 3 (21st June 2021) - Sheng, Mingwei; Lin, Yuanbang; Xu, Dongwei; Tian, Yizhu; Zhan, Yongqiang; Li, Changyong; Farmer, Douglas G.; Kupiec‐Weglinski, Jerzy W.; Ke, Bibo
Abstract : Background and Aims: The cluster of differentiation 47 (CD47)–signal regulatory protein alpha (SIRPα) signaling pathway plays important roles in immune homeostasis and tissue inflammatory response. Activation of the Hedgehog/smoothened (SMO)/GLI family zinc finger 1 (Gli1) pathway regulates cell growth, differentiation, and immune function. However, it remains unknown whether and how the CD47–SIRPα interaction may regulate Hedgehog/SMO/Gli1 signaling in mesenchymal stem cell (MSC)–mediated immune regulation during sterile inflammatory liver injury. Approach and Results: In a mouse model of ischemia/reperfusion (IR)–induced sterile inflammatory liver injury, we found that adoptive transfer of MSCs increased CD47 expression and ameliorated liver IR injury. However, deletion of CD47 in MSCs exacerbated IR‐induced liver damage, with increased serum ALT levels, macrophage/neutrophil infiltration, and pro‐inflammatory mediators. MSC treatment augmented SIRPα, Hedgehog/SMO/Gli1, and Notch1 intracellular domain (NICD), whereas CD47‐deficient MSC treatment reduced these gene expressions in IR‐stressed livers. Moreover, disruption of myeloid SMO or Notch1 increased IR‐triggered liver inflammation with diminished Gli1 and NICD, but enhanced NIMA related kinase 7 (NEK7) and NLR family pyrin domain containing 3 (NLRP3) activation in MSC‐transferred mice. Using a MSC/macrophage co‐culture system, we found that MSC CD47 and macrophage SIRPα expression were increased after LPS stimulation. The CD47‐SIRPα interaction increased macrophage Gli1 and NICD nuclear translocation, whereby NICD interacted with Gli1 and regulated its target gene Dvl2 (dishevelled segment polarity protein 2), which in turn inhibited NEK7/NLRP3 activity. Conclusions: The CD47‐SIRPα signaling activates the Hedgehog/SMO/Gli1 pathway, which controls NEK7/NLRP3 activity through a direct interaction between Gli1 and NICD. NICD is a coactivator of Gli1, and the target gene Dvl2 regulated by the NICD‐Gli1 complex is crucial for the modulation of NLRP3‐driven inflammatory response in MSC‐mediated immune regulation. Our findings provide potential therapeutic targets in MSC‐mediated immunotherapy of sterile inflammatory liver injury.